Thermophilic two-phase anaerobic digestion using an innovative fixed-bed reactor for enhanced organic matter removal and bioenergy recovery from sugarcane vinasse - Fuess, Lucas Tadeu; Kiyuna, Luma Sayuri Mazine; Ferraz, Antï¿½nio Djalma Nunes; Persinoti, Gabriela Felix; Squina, Fabio Marcio; Garcia, Marcelo Loureiro [UNESP]; Zaiat, Marcelo (Elsevier, 2017)
This study considered the application of anaerobic digestion (AD) with phase separation combined with the use of an anaerobic structured-bed reactor (ASTBR) as the methanogenic phase for the treatment of sugarcane vinasse, a high-strength wastewater resulting from ethanol production. Two combined thermophilic acidogenic-methanogenic systems formed by one single acidogenic reactor followed by two methanogenic reactors operated in parallel were compared, namely, a conventional UASB reactor and an upflow ASTBR reactor. Increasing organic loading rate (OLR) conditions (15–30 kg COD m−3d−1) were applied to the methanogenic reactors. The results highlighted the feasibility of applying the ASTBR to vinasse, indicating a global COD removal higher than 80%. The ASTBR exhibited a stable long-term operation (240 days), even for OLR values as high as 30 kg COD m−3d−1. The application of similar conditions to the UASB reactor indicated severe performance losses, leading to the accumulation of acids for every increase in the OLR. An energetic potential of 181.5 MJ for each cubic meter of vinasse was estimated from both hydrogen and methane. The provision of bicarbonate alkalinity proved to be a key factor in obtaining stable performance, offsetting the limitations of relatively low hydraulic retention times (<24 h).
Keywords: Bioenergy recovery; Biohydrogen; Innovative system; Long-term stable operation; Structured-bed reactor; Sugarcane vinasse